The HOSENG trial – Effect of the provision of oral self-testing for absent and refusing individuals during a door-to-door HIV-testing campaign on testing coverage: protocol of a cluster-randomized clinical trial in rural Lesotho - Alain Amstutz; Thabo Ishmael Lejone; Lefu Khesa; Josephine Muhairwe; Bienvenu Lengo Nsakala; Katleho Tlali; Moniek Bresser; Fiona Vanobberghen; Mathebe Kopo; Mpho Kao; Thomas Klimkait; Manuel Battegay; et al. (Trials, 2019)
Abstract Background HIV-testing coverage remains below the targeted 90% despite efforts and resources invested. Home-based HIV-testing is a key approach endorsed by the World Health Organization (WHO), especially to reach individuals who might not seek testing otherwise. Although acceptance of testing during such campaigns is high, coverage remains low due to absent household members. This cluster-randomized trial aims to assess increase in testing coverage using oral HIV self-testing (HIVST) among individuals who are absent or decline testing during home-based HIV-testing. Methods The HOSENG (HOme-based SElf-testiNG) trial is a cluster-randomized, parallel-group, superiority trial in two districts of Lesotho, Southern Africa. Clusters are stratified by district, village size, and village access to the nearest health facility. Cluster eligibility criteria include: village is in catchment area of one of the study facilities, village authority provides consent, and village has a registered, capable, and consenting village health worker (VHW). In intervention clusters, HIV self-tests are provided for eligible household members who are absent or decline HIV-testing in the presence of the campaign team. In control clusters, standard of care for absent and refusing individuals applies, i.e., referral to a health facility. The primary outcome is HIV-testing coverage among individuals aged 12 years or older within 120 days after enrollment. Secondary objectives include HIV-testing coverage among other age groups, and uptake of the different testing modalities. Statistical analyses will be conducted and reported in line with CONSORT guidelines. The HOSENG trial is linked to the VIBRA (Village-Based Refill of ART) trial. Together, they constitute the GET ON (GETting tOwards Ninety) research project. Discussion The HOSENG trial tests whether oral HIVST may be an add-on during door-to-door testing campaigns towards achieving optimal testing coverage. The provision of oral self-test kits, followed up by VHWs, requires little additional human resources, finances and logistics. If cost-effective, this approach should inform home-based HIV-testing policies not only in Lesotho, but in similar high-prevalence settings. Trial registration ClinicalTrials.gov, (ID: NCT03598686). Registered on 25 July 2018. More information is available at www.getonproject.wordpress.com.